Peningkatan Prestasi Belajar Siswa Sekolah Dasar Mata Pelajaran Pendidikan Agama Islam Materi Dua Kalimat Syahadat melalui Metode Talking Stick - Rita Meilani; Azizah Aryati (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: The low academic achievement of first-grade students at SD IT Ar-Ridho Palembang in Islamic Religious Education (PAI), particularly in the material on the two sentences of the creed, is due to teaching methods that are not active enough and are not suitable for the material. Objective: This study aims to determine whether the application of the Talking Stick method can improve student achievement in this material. Method: This study used Classroom Action Research (CAR) conducted in two cycles. Data were collected through formative tests to measure student learning achievement, as well as observations of teacher and student activities during the learning process. Results: The study demonstrated that the application of the Talking Stick method can enhance student engagement, make the learning process more interactive, and facilitate students' memorization and understanding of the two sentences of the shahada. Conclusion: The Talking Stick method is efficacious in improving student learning achievement while creating a fun and participatory learning atmosphere. Contribution: This study contributes an alternative active learning method that Islamic Education teachers can apply to improve the quality of learning and student learning achievement, especially in lower grades.